Metode Bercerita dengan Media Buku Cerita Bergambar Terhadap Perkembangan Bahasa Anak Usia Dini - Aisyah Aisyah; Herlina Herlina; Azizah Azizah; Wahira Wahira (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to find out the description of children's language skills after being given the storytelling method with picture storybook media, the description of the storytelling method with picture storybook media in the learning process, and the effect of the application of storytelling methods with picture storybook media on the language development of PAUD children. The type of research used in this study is the quantitative type. The design of this study is a quantitative research with an associative objective that explains the relationship (influence) of the variables of the storytelling method with picture story book media (X) on the language development of early childhood at the age of 5-6 years (Y). The data collection techniques used were observations, documentation, interviews, and questionnaires. The data analysis used was descriptive analysis, research instrument test, validity test and reliability test, simple linear regression analysis, hypothesis test, and determinant coefficient. The results of the study showed that based on the t-test, the significant value of 0.000 < out of 0.05 means that the storytelling method with picture storybook media has a significant and positive effect on the development of early childhood language at the age of 5-6 years. This means that the better the application of the storytelling method using picture storybooks, the more the child's language development will increase, both in the ability to listen, speak, enrich vocabulary, and understand the content of stories in learning activities.